Utilization of Sea Water as Source of Electrical Energy of Coastal People - Andri Kapuji Kaharian; Nani Sofroh; Didik Aribowo (Department of Electrical Engineering Education, Faculty of Teacher Training and Education, 2017)
In this modern era electricity needs have a huge surge. It can even be said that humans are very dependent on electrical energy. Power outages, disturbing public activities, disrupted traffic flows and even wider relationships between countries can also be affected due to power outages. For that need to be developed alternative energy sources. One of the most untapped ones is the energy of seawater. The energy generated from seawater has advantages, such as environmental friendliness, and does not require much funding. one sign that seawater contains electric current is the presence of a high element of Sodium Chloride (NaCl) and by H2O is decomposed into Na+ and Cl-. With the free charge particle, there is an electric current. Has been done research about sea water that is able to generate electrical energy, where seawater is a compound of NaCl, sea water is a solution of electrolyte with biggest solute. From the results of research conducted that the stress contained in 200 ml of sea water obtained 0,5V, and when added 50 grams of salt voltage increased to 0.8V. By researching the conversion of alternative energy, sea water to generate electricity can help supply electricity from the government to meet the electricity needs in coastal areas.